2022
DOI: 10.1177/05390184231158195
|View full text |Cite
|
Sign up to set email alerts
|

Are evaluative bibliometrics neoliberal? A historical and theoretical problematization

Abstract: In this article, we problematize the notion that the continuously growing use of bibliometric evaluation can be effectively explained by ‘neoliberal’ ideology. A prerequisite for our analysis is an understanding of neoliberalism as both denoting a more limited set of concrete principles for the organization of society (the narrow interpretation) or as a hegemonic ideology (the broad interpretation). This conceptual framework, as well as brief history of evaluative bibliometrics, provides an analytical framing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Daniel Rodgers (2018) similarly lamented that ‘[n]eoliberalism is the linguistic omnivore of our times, a neologism that threatens to swallow up all the other words around it’. Just recently, a study investigating the potential explanatory power of the term for understanding the long-term evolution of evaluative bibliometric systems in a set of societies found that ‘if used without clarification, “neoliberalism” is a concept too broad and diluted to be useful’ (Hammarfelt and Hallonsten, 2023: 414).…”
Section: Toward a Broad And Empirically Minded Working Definition Of ...mentioning
confidence: 99%
“…Daniel Rodgers (2018) similarly lamented that ‘[n]eoliberalism is the linguistic omnivore of our times, a neologism that threatens to swallow up all the other words around it’. Just recently, a study investigating the potential explanatory power of the term for understanding the long-term evolution of evaluative bibliometric systems in a set of societies found that ‘if used without clarification, “neoliberalism” is a concept too broad and diluted to be useful’ (Hammarfelt and Hallonsten, 2023: 414).…”
Section: Toward a Broad And Empirically Minded Working Definition Of ...mentioning
confidence: 99%
“…In many countries, regulators stand behind universities to provide them with legitimacy and resources (cf. Hammarfelt and Hallonsten, this volume). This also implies that regulators have strong interests in monitoring whether universities are following rules as well as in assessing how they are using resources (Musselin, 2013).…”
Section: Regulators and Evaluationsmentioning
confidence: 99%